2020
DOI: 10.1111/fwb.13609
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions modify density‐dependent salmonid recruitment: Insights into the 2016 recruitment crash in Wales

Abstract: 1. Understanding the effects of density-dependent and density-independent factors on recruitment is often inhibited by difficulties quantifying their relative contributions in highly variable recruitment data. Use of data-driven statistical methods with data that include one or more extreme recruitment events could help overcome these difficulties. 2. Juvenile Atlantic salmon and trout abundances in Wales have declined over the last 2 decades, and 2016 was a notably poor recruitment year in rivers around south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 73 publications
(145 reference statements)
2
15
0
Order By: Relevance
“…As other salmonid species spawn earlier than grayling, high winter flow events can be detrimental to early life-stages by causing egg wash-out (Warren et al, 2015) and have been shown to contribute to reduced survival of juvenile Atlantic salmon Salmo salar (Gregory et al, 2020). Consequently, it has been suggested that flow management, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As other salmonid species spawn earlier than grayling, high winter flow events can be detrimental to early life-stages by causing egg wash-out (Warren et al, 2015) and have been shown to contribute to reduced survival of juvenile Atlantic salmon Salmo salar (Gregory et al, 2020). Consequently, it has been suggested that flow management, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of winter flows on juvenile survival was relatively weak (perhaps because it did not capture variance in flows, discussed below), this finding suggests a need to reconcile habitat management strategies for salmonids with different life histories. As other salmonid species spawn earlier than grayling, high winter flow events can be detrimental to early life‐stages by causing egg wash‐out (Warren et al., 2015) and have been shown to contribute to reduced survival of juvenile Atlantic salmon Salmo salar (Gregory et al., 2020). Consequently, it has been suggested that flow management, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of all or some of these factors will most likely result in unfavourable conditions for egg development and subsequent recruitment. Gregory et al (2020) found that the 2016 salmon recruitment crash in Wales was most likely caused by the unfavourable combination of warm spawning temperatures, which can inhibit spawning, and higher flood frequencies during egg incubation and emergence, resulting in washouts of eggs and alevins. Such inclement conditions could become more common under future climate change.…”
Section: Current Status Of Threats To Salmonid Populations In Fresh Watermentioning
confidence: 99%
“…In 2016, juvenile salmon numbers in England and Wales were among the lowest on record, and it was speculated that these were caused by an unusually warm winter and wet spring (ICES, 2017). A recent study presented evidence suggesting that winter and spring temperatures and discharges were associated with this ‘2016 recruitment crash’ in seven rain‐fed rivers throughout Wales (Gregory et al ., 2020). We observed similarly low juvenile abundance in 2016 on the River Frome, a primarily groundwater‐fed chalk stream in southern England characterized by relatively benign temperature and discharge regimes (Berrie, 1992).…”
Section: Figurementioning
confidence: 99%
“…Following Gregory et al . (2020), a flood was defined as a high pulse when the discharge was between three and five times above the 50% (Q50) river level rate, and the number of floods during pre‐emergence and emergence was calculated from the discharge data. We used River Lab Long Term Monitoring (RLLTM) programme temperature data collected near the East Stoke gauging station (Supporting Information Figure S3) to calculate the mean water temperature during spawning and emergence.…”
Section: Figurementioning
confidence: 99%